Análise da resistência de prismas e pequenas paredes de alvenaria estrutural cerâmica para diferentes tipos de argamassas - Santos, Mauro Joel Friederich dos (2008)
This work has as main objective to analyze the influence of the ceramic block geometry in the mechanical performance of the structural masonry, under centered compression, when mortars with resistance varied are used. Two types of ceramic blocks geometries are studied: one with drained walls (BPV) and the other with solid walls (BPM), possessing approximate resistances of 30MPa, in relation to their liquid area; also four mortar lines with resistances between 4MPa and 17Mpa were used. The experimental program includes the following compression essays: units, prisms and small walls, in which five prisms of two and three overlapping rows and four small walls of two and half blocks were made by 4 height rows. Also, the module of elasticity, so much for the mortars, blocks and prisms, as for the small walls was obtained. Among the several essayed combinations, the variance analysis of the samples submitted to the compression was made. Based on the analysis of the results, it may be concluded that the BPM block, is more efficient for the use in structural masonry than the BPV one, when an increment in the resistance of the masonry is needed, increasing the mortar resistance; that efficiency may be defined in the relation of the prisms resistance (two and three blocks) and of the small walls by the block. The small walls built with BPM blocks present a significant capacity to absorb strains, when high resistance mortar is used (the one used in this work); as for the BPV block, that difference was not so expressive. Therefore, the use of placement mortar with those resistances may potentiate the ceramic blocks masonry, depending on the geometry and the mechanical properties of the adopted blocks.